CT angiography for the management of postpartum hemorrhage refractory to conservative treatment. (2nd November 2022) - Jung, Young Mi; Kim, Hyeon Ji; Choi, Won Seok; Park, Jee Yoon; Seong, Nak Jong; Oh, Kyung Joon; Hong, Joon-Seok; Yoon, Chang Jin
Abstract: Introduction: Postpartum hemorrhage (PPH) is one of the leading causes of maternal morbidity and mortality. Computerized tomographic (CT) angiography is a useful tool to identify hemorrhage from various conditions. However, the feasibility of CT angiography for the management of PPH has not been well evaluated. Objective: To evaluate the clinical usefulness of CT angiography in the management of PPH refractory to the conservative treatment. Methods: This retrospective cohort study consisted of 528 consecutive patients who were transferred to our institute after delivery at 28 primary maternity hospitals for the management of PPH between 2009 and 2017. Immediate intervention such as arterial embolization and hysterectomy were performed on 278 patients. Of the remaining 250 patients, CT angiography was performed on 61 patients with hemodynamic stability but with sustained hemorrhage refractory to medical treatment. The diagnostic index was assessed using conventional angiography as the reference standard. The clinical outcome was compared between patients with and without contrast extravasation on CT angiography. Results: (1) The prevalence of contrast extravasation was found in 61% of patients (37/61); (2) conventional angiography and arterial embolization were performed in 78% of patients (29/37) with contrast extravasation on CT angiography. Contrast extravasation was confirmed in 83% of patients (24/29) by conventional angiography; (3) among the 24 patients without contrast extravasation on CT angiography, 96% (23/24) were managed conservatively; (4) the patients with contrast extravasation on CT angiography received more packed red blood cell (PRBC) transfusion than those without that condition (7.3 ± 5.2 units vs. 3.8 ± 2.9 units, p = .009). Massive transfusion (defined as transfusion of 10 or more units of PRBC) was more common in patients with contrast extravasation than in those without (27% [10/37] vs. 0% [0/24], p = .004). Conclusions: Conservative treatment succeeded in 96% of patients without contrast extravasation on CT angiography. CT angiography is useful to identify patients requiring intervention in the management of hemorrhage refractory to medical treatment.